ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI VOLUME EKSPOR BIJI KAKAO INDONESIA KE MALAYSIA - Ilma Yuni Rosita; Lilis Imamah Ichdayati; Rizki Adi Puspita Sari (AGRIBUSINESS JOURNAL, 2019)
This study aims to analyze the factors that affect the volume of Indonesian cocoa exports to Malaysia. Multiple linear regression and ordinary least squares (OLS) were employed to analyze time series of data from 2005 until 2013. Based on the analysis, it is obtained that factors that significantly effect the volume of Indonesian cocoa exports to Malaysia with a significance level (α) five percent are the real prices of Indonesian cocoa exports to Malaysia and the real prices of cocoa beans the international market.